ANALYSIS OF DETERMINANTS OF SMOKING BEHAVIOR IN ADOLESCENTS BASED ON HEALTH BELIEF MODEL THEORY - Deddi, Rhandy Bane Umbu Dongu; Setyawan, Yuswanto (HEARTY, 2025)
Smoking behavior among adolescents remains a pressing public health concern due to its long-term health implications. This study aims to analyze the determinants of smoking behavior among senior high school students using the Health Belief Model (HBM) framework. A descriptive quantitative method was employed with a survey approach, and data were collected through a structured questionnaire. The sample consisted of 300 senior high school students selected through purposive sampling. The findings revealed that 40% of respondents were active smokers. A total of 63.4% demonstrated high perceived susceptibility to the health risks of smoking, while 36.6% showed low or uncertain risk perception. Additionally, 26.7% of students exhibited low self-efficacy in resisting cigarette offers from peers. These results indicate that perceived susceptibility and self-efficacy are critical factors influencing smoking behavior among adolescents. Health education interventions that enhance these two psychological aspects are essential to reduce smoking prevalence in this vulnerable age group.